Selecting indicator species for biodiversity management. Issue 10 (13th November 2018) - Bal, Payal; Tulloch, Ayesha IT; Addison, Prue FE; McDonald‐Madden, Eve; Rhodes, Jonathan R
Abstract : Indicator species are frequently used for biodiversity management but whether indicator species selection is explicit about their ability to improve management decisions remains unclear. We reviewed the scientific literature to assess whether existing methods for selecting indicator species account for the following five monitoring and management "decision factors": objectives, constraints, actions, uncertainties, and biodiversity outcomes. Of the selected studies, most focused only on improving monitoring efficiency rather than on management effectiveness, potentially leading to ineffective indicators for decision making; only 21% of the studies explicitly accounted for management objectives and actions. Crucially, 94% of the reviewed studies and one‐half of all indicator selection methods overlooked constraints (eg budgets), as well as uncertainties in indicator responses to management. To improve selection of indicator species, we suggest a systematic approach using key concepts from structured decision making. This approach facilitates explicitly evaluating management outcomes as part of the indicator species selection process and allows for the review of indicator choices over time to improve future monitoring and management decisions.